О факторах, определяющих структуру и функцию сосудов малого круга кровообращения у ряда наземных позвоночных - Антипчук, Ю.П. (Вестник зоологии, 1967)
The peculiarities of the histological structure of the small circle vessel walls of blood circulation in reptiles and mammals do not depend on the systematic position of these vertebrates, because within the narrow systematic units there are animals with different type of pulmonary vessel structure. The structural differentiation of the pulmonary arteries in reptiles cannot be explained by differentiations in blood saturation with oxygen because the blood flows in three-chamber heart are fully separated. The manner of life, degree of physical activity, domestication and peculiarities of pulmonary blood circulation affect the formation of structural peculiarities of the pulmonary vessels in repti-les and mammals in the process of evolution. Changes in the structure of vessel walls in animals ontogenesis appear as a result of animal stay at great altitude and age peculiarities of the development.